Kinetics of thermal decomposition of the polyester nanocomposites - Aydogmus, Ercan; Arslanoglu, Hasan (Taylor & Francis Inc, 2021)
In this study, characterization processes have been done by synthesizing the nano-aerosil-reinforced polyester composite. Chemical bonds formed in polyester composites were examined with FTIR spectrum and thermal stability with proportional integral derivative (PID) system. With the PID system, the drying kinetics of nano-polyester composites were examined from room temperature to 378 K, and thermal decomposition kinetics up to 918 K. The effect of temperature separates volatile components and physical impurities from the structure in the first region. Chemical decomposition starts in the second region, and degradation is the fastest step. Thermal degradation slows in the third region, and the remaining cross-linked components shift away from the structure. According to the new special solution method, the most suitable function in the thermal decomposition kinetics of polyester nanocomposites was found in the second-order model (f (delta) = (1-delta)(2), E: 53.492 kJ/mol, R-2: 0.99686, for experiment 3). Also, with three-dimensional diffusion and Jander functions have been found better results using Coats-Redfern method (R-2: 0.99882, E: 50.55141 kJ/mol for experiment 3). The most consistent results in drying kinetics of polyester nanocomposites were found in the Midilli and Kucuk model (R-2: 0.99575, RMSE: 0.03099 for experiment 1).
Keywords: aerosil; kinetic model; nanocomposite; polyester; thermal decomposition